Principal-agent relationship issues in Islamic banks: a view of Islamic ethical system. Issue 2 (10th April 2018) - Zainuldin, Mohd Haniff; Lui, Tze Kiat; Yii, Kwang Jing
Abstract : Purpose: This paper aims to discuss and explore the unique agency issues in Islamic banks which give rise to different agency conflicts exist in Islamic banks as compared to conventional banks. In addition, this paper critically examines agency theory in Islamic banking perspective by incorporating Islamic ethical considerations in the principal–agent setting. Design/methodology/approach: This is a conceptual paper, and the discussions revolve around the review of literature of which important sources have been cited in a way that demonstrates a reasonable understanding of the topic. It attempts to create a discourse around the inclusion of Islamic ethical system in understanding the governance structure of Islamic banks. Findings: This paper concludes that Islamic ethical system embedded in the Islamic banks business activities shapes Islamic banks into organisations that place higher ethical considerations than conventional banks. Therefore, Islamic banks are likely to have less severe agency problems relative to their conventional counterparts. Research limitations/implications: Because of the chosen research approach, the research results may lack generalisability. Therefore, researchers are encouraged to test the proposed propositions further. Practical implications: As the discourse generated by the paper, it can ultimately enhance the understanding of Islamic governance structure in the perspective of agency issues. Social implications: As the discourse generated by the paper, it can ultimately enhance the understanding of Islamic governance structure in the perspective of agency issues. Originality/value: The paper attempts to bring to attention the important aspect of principal–agent relationship within the Islamic banking structures and explain the role of incorporating Islamic ethical system in enhancing the understanding of the principal–agent relationship.